Answer:
The son is 20
The man is 60
Step-by-step explanation:
We can set up this equation with what we know. Let m stand for the Man's current age, and let s stand for his son's current age.
We know the Man's current age is three times that of his son, so this equation can be written as: m = 3s
Ten years ago means the man's current age minus 10 years. So it is m-10. So ten years ago he was 5 times his son's age 10 years ago, 5(s-10)
This can be written as: m-10=5(s-10)
Solve with either substitution or elimination, the choice is yours, it doesn't really matter which method you use. I'll be using substitution.
m-10=5(s-10)
3s-10= 5s-50
40=2s
20 = s
The son is 20 years old.
We know the man is currently 3 times his son's age, because m=3s, so just solve for m since you now know the value of s.
m=3s
m=3(20)
m=60
The man is 60 years old